Linguistic Politeness in Indonesian Language Learning Interactions: A Pragmatic Analysis Based on Leech’s Principles - Farayanti, Dana; Suparni, Suparni; Syamsuddin, Syamsuddin (Applied Linguistics: Innovative Approaches and Emerging Trends, 2024)
This study aims to describe the forms of linguistic politeness exhibited by tenth-grade students during Indonesian language learning interactions at SMA Negeri 1 Tomini. Employing a descriptive qualitative approach and grounded in Geoffrey Leech’s theory of politeness maxims, the research identified six types of maxims reflected in student utterances: tact, generosity, approbation, modesty, agreement, and sympathy. Data were collected through observation, documentation, interviews, and a listening-note technique. The findings reveal that politeness is an integral aspect of student communication in the classroom and plays a significant role in fostering a harmonious, cooperative, and respectful learning environment. Furthermore, the use of polite language is influenced by students’ social surroundings and family backgrounds. This study underscores the importance of reinforcing politeness values in educational settings and contributes to the development of language learning grounded in pragmatic principles.